Genomic crossroads between non-Hodgkin’s lymphoma and common variable immunodeficiency - Guevara-Hoyer, Kissy; Fuentes-Antrás, Jesús; de la Fuente-Muñoz, Eduardo; Fernández-Arquero, Miguel; Solano, Fernando; Pérez-Segura, Pedro; Neves, Esmeralda; Ocaña, Alberto; Pérez de Diego, Rebeca; Sánchez-Ramón, Silvia (Frontiers in Immunology, 2022)
Common variable immunodeficiency (CVID) represents the largest group of primary immunodeficiencies that may manifest with infections, inflammation, autoimmunity, and cancer, mainly B cell non-Hodgkin’s lymphoma (NHL). Indeed, NHL may result from chronic or recurrent infections and has therefore been recognized as a clinical phenotype of CVID, although rare. The more one delves into the mechanisms involved in CVID and cancer, the stronger the idea that both pathologies can be a reflection of the same primer events observed from different angles. The potential effects of germline variants on specific somatic modifications in malignancies suggest it might be possible to anticipate critical events during tumor development. In the same way, a somatic alteration in NHL could be conditioning a similar response at the transcriptional level in the shared signaling pathways with genetic germline alterations in CVID. We aimed to explore the genomic substrate shared between these entities to better characterize the CVID phenotype immunodeficiency in NHL. By means of an in silico approach, we interrogated the large, publicly-available datasets contained in cBioPortal for the presence of genes associated with genetic pathogenic variants in a panel of 50 genes recurrently altered in CVID and previously described as causative or disease-modifying. We found that 323 (25%) of the 1,309 NHL samples available for analysis harbored variants of the CVID spectrum, with the most recurrent alteration presented in NHL occurring in PIK3CD (6%) and STAT3 (4%). Pathway analysis of common gene alterations showed enrichment in inflammatory, immune surveillance, and defective DNA repair mechanisms similar to those affected in CVID, with PIK3R1 appearing as a central node in the protein interaction network. Co-occurrence of gene alterations was a frequent phenomenon. This study represents an attempt to identify common genomic grounds between CVID and NHL. Further prospective studies are required to better know the role of genetic variants associated with CVID and their reflection on the somatic pathogenic variants responsible for cancer, as well as, to characterize the CVID-like phenotype in NHL, with the potential to influence early CVID detection and therapeutic management.